The lost island of Tamarind - Aguiar, Nadia (Feiwel and Friends, 2008)
Thirteen-year-old Maya, who has spent her life at sea with her marine biologist parents, yearns for a normal life, but when a storm washes her parents overboard, life becomes anything but normal for Maya, her younger brother and baby sister, as they land at a mysterious, uncharted island filled with danger.